Professional development of EFL teachers through constructivist-oriented training programs - Pham Thi Kieu Oanh; Nguyen Van Trao; Nguyen Thi Hong Nhung (Institute of Advanced Engineering and Science, 2026)
Despite increasing policy endorsement of constructivist-oriented (CO) teacher training, limited empirical evidence has clarified how such programs reshape English as a foreign language (EFL) teachers’ beliefs and classroom enactment under curriculum reform. This study examines the influence of CO teacher training programs on the professional development (PD) of secondary English teachers in Vietnamese general education. A sequential explanatory mixed-methods design was adopted to capture both general patterns and nuanced forms of change. Quantitative data were collected from 192 secondary English teachers through a questionnaire survey to identify patterns in teachers’ beliefs, reported practices, and perceived contextual constraints, while qualitative data were obtained from 22 teachers through semi-structured interviews, classroom observations, lesson plan analysis, and reflective journals to provide triangulated classroom-based evidence. Findings reveal that belief-level endorsement was more consistent than sustained pedagogical restructuring, particularly in assessment for learning (AfL) practices. Teachers increasingly reconceptualized their roles as facilitators and demonstrated greater attention to learning task design, classroom interaction, and competency-aligned assessment. However, the enactment of constructivist teaching (CT) remained uneven and was shaped by contextual constraints such as large class sizes, limited instructional time, and curriculum-related pressures. The study conceptualizes PD as a non-linear and contextually mediated process. By integrating large-scale survey data with sustained classroom-based qualitative documentation, this research offers triangulated and context-sensitive empirical evidence from a reform-driven EFL system, contributing nuanced insight to international scholarship on teacher PD.